Mengukur Kinerja Perusahaan: Menggunakan Metode Pendekatan Balanced Scorecard - Nurjanah; Sukaesih, Evi; Rachman, Andry Arifian (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This research aims to look at the company's performance using the balanced scorecard method, which will be measured using a financial perspective, customer perspective, internal business perspective and performance learning and growth perspective, the research method uses a descriptive analysis research method with quantitative descriptive approach, the research results show that the company's performance uses a perspective approach. The higher the financial percentage of the current ratio, the more liquid the financial condition of the research object is, while the company's performance using a customer perspective means that the revenue generating index increases, the service gets better, while the financial performance measured using the customer business method shows that Minimize Error Rate and Rework (MERR)The smaller it is, the smaller the error in the service system. Results of Prime Plaza Hotel Purwakarta in 2021 using a balanced scorecard for the Learning and Growth perspective, Prime Plaza Hotel Purwakarta got a meaning Fair/Average.